Perancangan Sistem Informasi Pembelajaran Online (E-Learning) Berbasis Web - Bambang Kurnia; Tumini Tumini (Lembaga Pengembangan Kinerja Dosen, 2023)
Education is a basic human need that constantly transforms and updates in line with developments in all aspects of life. Changes and improvements in the world of education encompass various components, including teacher competence, educational quality, curriculum, infrastructure, educational management, as well as innovative teaching methods and strategies. The limitation of time in school often becomes the cause of restricted material delivered by teachers. Additionally, when teachers are unable to attend classes, it results in difficulties for students in accessing materials for learning. This system involves various inputs, such as student data, teacher data, class data, subject data, teaching schedule data, lesson material data, assignment data, student registration data, and assignment answer data. The outputs of this system include reports on student data, teacher data, classes, subjects, teaching schedules, lesson materials, assignment grades, and assignment grade data. This e-learning application is developed using the PHP programming language and utilizes the MySQL database in this Final Project.